THE EFFECT OF TASTE AND PACKAGING ON BRAND LOYALTY OF TRADITIONAL SNACKS, SAMBO LAUGHING BREAD - Liharman Saragih; Adelya Husnul Khotimah; M.Farhan Abdus Sattar; Siti Azzahra Surin; Fingki Tria Bila (Jurnal Review Pendidikan dan Pengajaran, 2026)
This study aims to empirically examine the influence of taste and packaging on brand loyalty of Sambo Laughing Bread among students at the Faculty of Economics, Simalungun University. Sambo Laughing Bread is a superior local product facing competition from modern snacks on campus. The research method used was quantitative with a survey approach. The sample size was 30 respondents, drawn from active students of the Faculty of Economics through accidental sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression.The partial results indicate that: Taste has a significant influence on brand loyalty, confirming that Sambo's crunchy texture and distinctive sesame flavor are the main reasons for consumers to make repeat purchases.Packaging has a positive but slightly lower influence than taste, indicating that although the product's protective function is good, design innovation is needed to enhance its visual appeal to the younger generation. Simultaneously, both variables significantly influence brand loyalty, with a coefficient of determination (R2) indicating the independent variable's contribution in explaining consumer loyalty. The results of this study recommend that Sambo Laughing Bread management maintain its authentic taste while modernizing its packaging to strengthen its brand identity in the academic market.